2005
DOI: 10.1523/jneurosci.1200-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bax Gene Deletion on Muscle and Motoneuron Degeneration in a Sexually Dimorphic Neuromuscular System

Abstract: Motoneurons in the spinal nucleus of the bulbocavernosus (SNB) and their target muscles in the perineum, bulbocavernosus (BC), and levator ani (LA) normally degenerate in female rodents. Death of the motoneurons and muscles can be prevented by androgen treatments around the time of birth. To identify the intracellular mechanisms underlying hormone-dependent survival of this neuromuscular system, we examined mice with a targeted disruption of the pro-death gene Bax. SNB motoneuron number was increased in female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 44 publications
1
40
1
Order By: Relevance
“…Fluorogold injections into the whisker pads labeled significantly more facial MNs in the Bax KO (30%; p Ͻ 0.01) (data not shown), suggesting that many of the excess facial MNs innervated their targets (see also Jacob et al, 2005). Although the significant increase in retrogradely labeled facial MNs in the Bax KO suggests that many rescued cells may have formed synaptic contacts, because we did not attempt to directly quantify neuromuscular (2) n.d.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Fluorogold injections into the whisker pads labeled significantly more facial MNs in the Bax KO (30%; p Ͻ 0.01) (data not shown), suggesting that many of the excess facial MNs innervated their targets (see also Jacob et al, 2005). Although the significant increase in retrogradely labeled facial MNs in the Bax KO suggests that many rescued cells may have formed synaptic contacts, because we did not attempt to directly quantify neuromuscular (2) n.d.…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies of motor systems developing with reduced PCD have reported more cell bodies in central motor nuclei or more axons in cranial or spinal roots , but with the exception of paralytic chicks and mice (Ding et al, 1983;Oppenheim and Chu-Wang, 1983;Landmesser, 1992;Misgeld et al, 2002), whether rescued MNs project to their muscle targets has not been systematically examined Jacob et al, 2005). In cross sections of adult peripheral hindlimb and cranial nerves (mixed motor and sensory) of Bax KO and MyoGDNF mice (and in the paralyzed embryonic chick), we observed more (ϳ 40 -50%) myelinated axons in close proximity to their muscles compared with WT mice or vehicle-treated chick embryos (Table 1, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although an LA muscle was present in every adult female Great Wistar rat examined (Tobin and Joubert, 1988), no LA fibers were found in the majority of Sprague Dawley rats examined, based on microscopic analysis of serial sections through the perineum (Bengston et al, 1996). In mice, the LA of adult females is miniscule, averaging only about 50 fibers (Jacob et al, 2004). Moreover, although cell addition and growth undoubtedly contribute to the sex difference in LA size, several observations suggest that cell death also plays an important role in sexual differentiation of both the LA and BC muscles.…”
Section: Androgen Effects On the Bc/la Muscles Androgen-dependence Ofmentioning
confidence: 99%
“…We find TUNEL-positive cells in the BC and LA muscles of both sexes perinatally, but the density of apoptotic cells is significantly greater in females (Figure 4; Jacob and Forger, unpublished). Moreover, LA muscle fiber number is increased in female mice lacking the pro-death gene, Bax (Jacob et al, 2004), and is massively increased in double knockout mice lacking Bax and Bak, two genes critical for cell death in many tissues (Jacob, Ray, Lindsten and Forger, unpublished). Thus, cell death contributes to sexual differentiation of the LA, at least in mice.…”
Section: Androgen Effects On the Bc/la Muscles Androgen-dependence Ofmentioning
confidence: 99%